Coal ash Portland Cement Mortars Sulphate Resistance - Esperanza Menéndez; Cristina Argiz; Miguel Ángel Sanjuán (Civil Engineering Journal, 2021)
Coal fly ash (CFA), coal bottom ash (CBA) are residues produced in thermo-electrical power stations as result of the coal combustion in the same boiler. Therefore, some characteristics of the coal fly ash (CFA) are comparable with those of the coal bottom ash (CBA). Nevertheless, coal bottom ash size is larger than coal fly ash one. Consequently, it was found that it is necessary to grind the coal bottom ash (CBA) to reach a similar size to that one of the CFA. The objective of this paper is to evaluate the performance of Portland cement mortars made with coal fly ash (CFA), coal bottom ash (CBA) or mixes (CFA+CBA), against sulphate attack. The methodology is based on the expansion of slender bars submerged in a sodium sulphate solution (5%) according to the ASTM C-1012/C1012-13 standard. It has been found that mortars elaborated with CEM I 42.5 N (without ashes) presented the largest expansion (0.09%) after a testing period of 330 days. Mortars made with CEM II/A-V exhibited lower expansion (0.03%). Summing up, it can be established that mortar expansion decreases when the coal ash amount increases, independently of the type of coal ash employed. The novelty of this paper relies on the comparison between the performances of Portland cement mortars made with coal fly ash (CFA) or coal bottom ash (CBA) exposed to external sulphate attack. Doi: 10.28991/cej-2021-03091640 Full Text: PDF